A Comparative Study on the Predictive Value of Different Resting-State Functional Magnetic Resonance Imaging Parameters in Preclinical Alzheimer's Disease - Wang, Sheng-Min; Kim, Nak-Young; Kang, Dong Woo; Um, Yoo Hyun; Na, Hae-Ran; Woo, Young Sup; Lee, Chang Uk; Bahk, Won-Myong; Lim, Hyun Kook (Frontiers in Psychiatry, 2021)
Objective Diverse resting-state functional magnetic resonance imaging (rs-fMRI) studies showed that rs-fMRI might be able to reflect the earliest detrimental effect of cerebral beta-amyloid (Aβ) pathology. However, no previous studies specifically compared predictive value of different rs-fMRI parameters in preclinical AD. Methods A total of 106 cognitively normal adults (Aß+ group=66 and Aß- group=40) were included. Three different rs-fMRI parameter maps including functional connectivity (FC), fractional amplitude of low-frequency fluctuations (fALFF), and regional homogeneity (ReHo) were calculated. Receiver operating characteristic (ROC) curve analyses was utilized to compare classification performance of the three rs-fMRI parameters. Results Overall, the classification accuracies were acceptable for the three rs-fMRI parameters. The best performance was achieved when FC maps were employed (AUC, 0.915, p < 0.001). Good but weaker performance was achieved by using ReHo maps (AUC, 0.836, p < 0.001) and fALFF maps (AUC, 0.804, p < 0.001). The brain regions showing the greatest discriminative power included left angular gyrus for FC, left anterior cingulate for ReHo, and left middle frontal gyrus for fALFF. Conclusion Our results strengthen the idea that rs-fMRI might be sensitive to earlier changes in spontaneous brain activity and FC in response to cerebral Aβ retention. However, further longitudinal studies with larger sample size are needed to confirm their utility in predicting the risk of AD.